Effects of design parameters on fracture resistance of glass simulated dental crowns. Issue 3 (March 2016) - Zhang, Zhongpu; Sornsuwan, Tanapon; Rungsiyakull, Chaiy; Li, Wei; Li, Qing; Swain, Michael V.
Highlights: XFEM results were in good agreement with those of the experimental results. XFEM enabled us to capture a more accurate load at first sign of a crown's failure. Increasing margin thickness will increase fracture resistance of all-ceramic crown. Decreasing convergence angle is recommended to enhance fracture resistance. Adding an adhesive layer will enhance fracture resistance according to XFEM results. Abstract: Objective: This study aimed to individually quantify the effects of various design parameters, including margin thickness, convergence angle of abutment, and bonding conditions on fracture resistance of resin bonded glass dental crown systems (namely, glass simulated crown). Materials and methods: An in vitro experimental test and an in silico computational eXtended Finite Element Method (XFEM) were adopted to explore crack initiation and propagation in glass simulated crown models with the margin thickness ranging from 0.8 to 1.2 mm, convergence angle from 6° to 12°, and three different bonding conditions, namely non-bonded (NB), partially bonded (PB), fully bonded (FB). Results: The XFEM modeling results of cracking initiation loads and subsequent growth in the glass simulated crown models were correlated with the experimental results. It was found that the margin thickness has a more significant effect on the fracture resistance than the convergence angle. The adhesively bonded state has the highest fracture resistance among these three different bonding conditions. Conclusion: Crowns with thicker margins, smaller convergence angle and fully bonded are recommended for increasing fracture resistance of all-ceramic crowns. This numerical modeling study, supported by the experimental tests, provides more thorough mechanical insight into the role of margin design parameters, thereby forming a novel basis for clinical guidance as to preparation of tapered abutments for all-ceramic dental crowns.